Rechallenge with EGFR-TKI after failure of immunotherapy is considered an effective treatment for advanced lung adenocarcinoma patients with EGFR exon 19 deletion: a case report - Chen, Shubin; Yu, Qitao; Jiang, Wei; Lu, Yukun; Zhao, Yun; Wang, Huilin (Frontiers in Medicine, 2023)
In advanced lung adenocarcinoma patients with epidermal growth factor receptor (EGFR) mutation, epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) have an excellent and long-lasting therapeutic response, but virtually all patients eventually develop drug resistance and experience disease progression. The use of immunotherapy after EGFR-TKIs may be a successful therapeutic option for individuals who are resistant to them. It's still unclear if EGFR-TKIs can be administered again when immunotherapy failed. We describe the case of a 37-year-old woman who was found to have T4N3M1a stage IVa lung adenocarcinoma. Amplification refractory mutation system PCR (ARMS-PCR) genetic testing suggested EGFR exon 19 deletion. The patient was initially treated with the regimen of icotinib 125mg tid combined with anlotinib 8mg qd d1-d14 with an optimal efficacy rating of partial response (PR) and was granted a PFS of 7 months. In secondline treatment, the patient received three cycles of KN046(KN046 is a bispecific antibody inhibitor of PD-L1 and CTLA-4) 295mg d1 plus pemetrexed 800mg d1 plus carboplatin 750mg d1 regimen with an optimal efficacy rating of stable disease (SD) on CT. The third-line therapy was decided to be afatinib with docetaxel and the patient was evaluated for PR on CT. Dated until 15 August 2022, the patient got a progression free survival (PFS) of 14 months. The successful treatment of this patient was a reminder that EGFR exon 19 deletion patients with EGFR-TKI resistance failing with immunotherapy followed by EGFR-TKI rechallenge may be effective.